Bridging Cultural Gaps: Enhancing Communication in Medical Emergency Teams to Improve Patient Safety - Khalaf Maged Alotaibi; Muhammad Hussein Al-Ghannam; Mohammed Qaed Maysha Alotaibi; Abdulrahman Abdullah Almutib; Majed Mohammed Qazi Al Otaibi; Khaled Salbi Almorshedy Alotaibi; Abdullah Saud Alsahli; Saud Ammar Helal Almutairy; Saud Abdullah Salah Alotaibi; Mohamd sade Alsahli (International Journal of Medical Toxicology and Legal Medicine, 2024)
This essay investigates the critical role of cultural communication in optimizing the effectiveness of medical emergency teams. Building upon the observation that communication failures are a primary contributor to adverse events and near misses, this study explores the multifaceted nature of these challenges. While language barriers are a significant factor, cultural communication encompasses a broader spectrum of issues. These include The urgency and high-stakes nature of acute medical care exacerbate the impact of these communication barriers. Rapidly evolving patient conditions demand swift, accurate decision-making and coordinated teamwork. Cultural differences can significantly influence these critical processes, impacting judgment and potentially increasing the risk of medical errors. This study posits that a deeper understanding of cultural communication within medical emergency teams is crucial for enhancing patient safety and improving the quality of acute care delivery.